Measuring Intellectual Capital and Its Impact on Financial Performance: Empirical Evidence from CNX Nifty Companies. (August 2016) - Tandon, Kamini; Purohit, Harsh; Tandon, Deepak
During the recent years, value of financial assets has grown exponentially when compared to physical assets indicating that intangibles are growing in importance in their contribution to economic growth. The evidence in support of this phenomenon can be found in the increasing gap between market and book valuation of firms. The present study attempts to measure the intellectual capital (IC) of publicly listed firms in India and empirically examine the relationship among IC, financial performance and market valuation of these firms. Value creation efficiency of the firms listed on CNX Nifty over the period ranging from 2004–2005 to 2013–2014 has been estimated using Pulic's Value Added Intellectual Coefficient (VAIC). It was observed that firms operating in sectors such as financial services, mining and energy had the highest VAIC scores. Further, there was a positive association between VAIC and all the measures of financial performance—profitability, productivity and market valuations. Efficiency of physical capital employed had a significant positive relation with profitability, market valuation as well as productivity. Human capital efficiency was found to have a strong positive association with profitability, while structural capital efficiency did not have any significant impact on any of the measures of financial performance.